EFEKTIFITAS ETHREL DALAM PENINGKATAN PRODUKSI MENTIMUN (Cucumis sativus L.) - Maizar Maizar (UIR Press, 2013)
The research was carried out at the experimental farm of Faculty of Agriculture Riau Islamic University Pekanbaru from January to April 2010. The aim of this research was to know ethrel affectivity and to determine optimum doses of ethrel use for enhancing cucumber production. The completely randomized design was used in this research, consisting of seven treatments with three replications. The ethrel doses given were: 0.0; 2.5; 5.0; 7.5; 10.0; 12.5 and 15.0 cc/l of water. Results showed that the ethrel given to cucumber plant can prolong the period of the plant vegetative growth, reduce the number of the male flower per plant, increase the number of the female flower per plant, increase the number of fruit per plant, increase weight of fruit per plant and per plot, and weight of dry matter per plant. The average of fruit length had no significantly effect. The best ethrel dose was 5 cc/l of water for enhancing cucumber production.